Development of educational booklet to the production of the self-care on individual with Diabetes mellitus in the rural area (Research, Society and Development, 2021)
The objective is to describe the building and validation of an educational booklet entitled: “Diabetes in a rural area: knowing the disease to prevent complications”. This is a methodological study developed at Santa Catarina west, product of the professional master’s in Nursing on Primary Health Care. The booklet content was based on Brazilian Society of Diabetes Guidelines and on the weakness on the self-care in the individual with diabetes living in a rural area through the application of a questionnaire. The booklet validation process involved judges with experience in the assistance to rural population by means of a questionnaire via Google Forms, containing a set of items related to content, validated by Content validity Index, considering the values above 80% as valid. The final version  printed of the booklet has 56 pages, front and back, and size 260x185mm, containing: cover, back cover, summary, presentation and five chapters. Altogether, 11 judges participated of this technology validation, which reached Validity of Content Index of 90%. It is concluded that this material is relevant and it is presented as knowledge provider and encourager of the self-care through the empowerment of this population.